NEW COMBINATIONS IN THE FERNS OF THAILAND - Lindsay, S.; Middleton, D. J. (Edinburgh Journal of Botany, 2009)
New combinations are made in the fern genera Colysis, Cyclosorus, Haplopteris and Selliguea from Thailand. A new combination for Pteridaceae subfamily Cryptogrammoideae is made.